1995
DOI: 10.1021/bi00045a013
|View full text |Cite
|
Sign up to set email alerts
|

Fourier Transform Infrared Difference Spectroscopy of Secondary Quinone Acceptor Photoreduction in Proton Transfer Mutants of Rhodobacter sphaeroides

Abstract: In order to investigate the changes of protonation or environment of carboxylic residues occurring upon photoreduction of the secondary quinone acceptor (QB) in the reaction center (RC) of the photosynthetic bacteria Rhodobacter sphaeroides 2.4.1., we have performed light-induced Fourier transform infrared (FTIR) spectroscopy on RCs from wild-type (Wt) and several site-directed mutants. The FTIR QB-/QB spectra have been obtained at pH 7 upon single-saturating flash excitation for native RCs and RC mutants cont… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

26
176
1

Year Published

1998
1998
2012
2012

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 102 publications
(203 citation statements)
references
References 36 publications
26
176
1
Order By: Relevance
“…For a given sample, these measurements were repeated over ∼30 h. Spectra are an average of two to three samples. , C-O-CH 3 at 1265 and 1290 cm -1 ), and the protein at 1728, 1685, 1651, 1641, 1554, 1537, 1527, and 1514 cm -1 (14,42,44). Among the series of L209 mutants, the Q B -/Q B spectrum of Thr-L209 RCs (Figure 2b) is the only one that is close to that of native RCs.…”
Section: Methodsmentioning
confidence: 87%
See 2 more Smart Citations
“…For a given sample, these measurements were repeated over ∼30 h. Spectra are an average of two to three samples. , C-O-CH 3 at 1265 and 1290 cm -1 ), and the protein at 1728, 1685, 1651, 1641, 1554, 1537, 1527, and 1514 cm -1 (14,42,44). Among the series of L209 mutants, the Q B -/Q B spectrum of Thr-L209 RCs (Figure 2b) is the only one that is close to that of native RCs.…”
Section: Methodsmentioning
confidence: 87%
“…Both spectra of Phe-L209 ( Figure 2d In all the mutant spectra (Figure 2), contributions from the methoxy groups of Q B are consistently detected at ∼1290 and 1265 cm (14,(19)(20)(21). , and 1400 and 1200 cm -1 which are not affected by the binding of labeled quinone, correspond mostly to the absorption of protein and unlabeled quinone (methyl, methoxy, and isoprenoid chain) groups.…”
Section: Q Bmentioning
confidence: 88%
See 1 more Smart Citation
“…However, at pH 7.8, in the presence of 1 mM Cd 2+ concentration, k AB (1) is much more reduced in the L209PY mutant (∼120 s -1 ; ∼75 times) than in the WT (∼700 s -1 ; ∼10 times). k AB (1) is mainly governed by the protonation state of L212Glu (17,(28)(29)(30). We have previously suggested that the L209PY mutantion may have disorganized the hydrogen-bond network involving water molecules and protonatable groups, which may serve as proton provision for L212Glu (24).…”
Section: Discussionmentioning
confidence: 99%
“…The partial protonation events that occur on Q A Ϫ and Q B Ϫ formations have been studied by spectroscopic techniques by using site-directed mutagenesis (9)(10)(11)(12)(13)(14)(15)(16)(17)(18)(19)(20)(21)(22) and by numerical methods (23)(24)(25)(26)(27)(28)(29)(30). There is a general agreement that the major response of the protein to the Q B Ϫ formation is the change of the ionization state of acidic residues situated in the Q B environment.…”
mentioning
confidence: 99%